Functionalized hexagonal boron nitride sheets and charge triggered interpenetrating polymer network based membranes work in tandem towards water remediation - Avasarala, Sankeerthana; Sen Gupta, Ria; Goyal, Priyanka; Bose, Suryasarathi (Environmental science water research & technology, 2024)
Imparting antifouling characteristics to water treatment membranes while delivering high pure water flux and high pollutant rejection has been a subject of significant research interest. In this study, we have adopted a unique approach combining a mixed matrix membrane strategy with interpenetrating polymeric networks to develop stimuli-responsive membranes that exhibit superior antifouling performance. Our process involves integrating functionalized hexagonal boron nitride into a polyvinylidene fluoride and polydopamine interpenetrating network membrane. The resulting membranes demonstrate high pure water flux, effective dye rejection over multiple runs, and excellent resistance to fouling. This integration enhances the tunability of membrane properties such as charge, hydrophilicity, and membrane morphology. The membranes were thoroughly characterized by microscopy and spectroscopy techniques. The membranes could be triggered to attain a negative or a positive charge by immersion in NaOH and HCl solutions, respectively. The membranes demonstrated stable dye rejection performance over multiple cycles of operation. A rejection rate of over 97% was observed for both methylene blue (cationic) and methyl orange (anionic) dyes over multiple rejection cycles. Even after continuous operation with bovine serum albumin, the membranes maintained a 90% flux recovery ratio. With these attributes in place, these fouling-resistant membranes have the potential to emerge as the next generation stimuli-responsive, fouling-resistant membranes with improved remediation efficiency. Charge triggered membranes demonstrate excellent resistance to fouling and high rejection rates towards charged dyes.